Anti-fibrotic effects of brevilin A in hepatic fibrosis via inhibiting the STAT3 signaling pathway. (1st June 2021) - Park, Yong Joo; Jeon, Mi Seon; Lee, Seulah; Kim, Jung Kyu; Jang, Tae Su; Chung, Kyu Hyuck; Kim, Ki Hyun
Graphical abstract: Abstract: Hepatic fibrosis is a chronic liver disease characterized by the accumulation of extracellular matrix (ECM). Activation of hepatic stellate cells (HSCs) after repetitive liver damage is a key event in hepatic fibrogenesis. As part of ongoing research projects to identify pharmacologically effective natural products, the phytochemical investigation of a MeOH extract of Centipeda minima led to the isolation of a sesquiterpene lactone, brevilin A, which was explored to elucidate potential anti-fibrotic effects by reversing HSC activation. First, we observed that transforming growth factor (TGF)-β1 treatment significantly increased the expression levels of HSC activation marker, α-smooth muscle actin (α-SMA), and ECM protein such as collagen and fibronectin. Then, we demonstrated that brevilin A reversed the TGF-β1-induced increase in protein and mRNA expression levels of α-SMA and collagen. To investigate the underlying molecular mechanism of brevilin A, we evaluated the effects of brevilin A on the STAT3 signaling pathway. STAT3 phosphorylation, increased by TGF-β1 treatment, was strongly inhibited by brevilin A; the expression levels of fibronectin and connective tissue growth factor were also significantly decreased by brevilin A. The present study indicated that brevilin A has a preventive and therapeutic potential against hepatic fibrosis.